Training of trainers stem build program for primary science teachers: An initiative towards stem education in school - Rose Amnah, A.R. (2017)
STEM education in Malaysia is still in its infancy and initiatives to increase STEM field participation were outlined in the Malaysian Blueprint 2013-20125. STEM initiatives is a continuous process starting from preschool until tertiary level to ensure participation in the STEM fields hence providing STEM workforce. Therefore, it is necessary for teachers to be equipped with knowledge and teaching approach for STEM education especially from primary school because this is the foundation and build connection science with the real life situation. This is to ensure that the mindset towards STEM fields can be cultivated and sown from early schooling level. Primary science teachers were given a three phase training program to on STEM pedagogical approach in implementing STEM activities in school. Thus, this paper will share experiences of how the training was implemented and the impact obtained by the teachers readinessn to implement STEM education in primary schools. teachers showed effort and confidence to carry out the activity but needs more training on the STEM pedagogical approach.